COVID-19 Pandemic Worsening Gender Inequalities for Women and Girls in Sub-Saharan Africa - Ahinkorah, Bright Opoku; Hagan, John Elvis; Ameyaw, Edward Kwabena; Seidu, Abdul-Aziz; Schack, Thomas (Frontiers in Global Women's Health, 2021)
Pandemics such as COVID-19 have often resulted in international, national and sub-regional crises, with considerable inequities across many societies. With the already existing structural and socio-economic inequalities in sub-Saharan Africa, the stay-at-home orders, lockdowns, and shutdowns across the sub-regional states could worsen and have a tremendous impact on vulnerable groups. Numerous studies across a variety of contexts have well-documented gender, and cultures on varied health outcomes. However, these have not been contextualized in sub-Saharan Africa in the light of the COVID-19 pandemic. This mini review discusses the ways by which COVID-19 has impacted the lives of girls and women across sub-Saharan Africa and the strategies that can help mitigate these challenges. The mini review specifically shares light on a wide array of dimensions where the inequities exist. These include the disproportionate areas affected by COVID-19; household inequities; educational inequalities; work/employment inequalities; disparities related to healthcare, sexual and reproductive health as well as housing inequities. Conclusively, the review accentuates the need for sub-Saharan African countries to adopt low-cost preventive measures such as discouraging mass gatherings (e.g., local community gatherings), and face masking with non-medical cloth like masks for the local populace as these are crucial in managing the spread of the virus among disproportionate women population. For localities with limited access to handwashing facilities, alternative strategies like alcohol-based hand rub solutions could be deployed. The complex interrelated disparities require a broad set of policy actions to lessen the current burden faced by many women in sub-Saharan Africa.